Influencing Factors of Stock Price in Nepal - Thapa, Krishna Bahadur (NCC Journal, 2019)
This paper explores the influencing factors of stock price in Nepal (with reference to Nepalese commercial banks) listed on the Nepal Stock Exchange Ltd. over the period of 2008 to 2018AD. The information were collected from questionnaire and financial statement of concerned organizations and analyzed using simple linear regression model. The conclusions of the work revealed that earning per share (EPS), dividend per share (DPS), effective rules and regulations, market whims and rumors, company profiles and success depend upon luck have the significant positive association with share price while interest rate (IR) and price to earnings ratio (PER), showed the significant inverse association with share price. Further, accessibility of liquidity, fundamental and technical analysis stimulates the performance of the Nepalese stock market. More importantly, stock market has been found to respond significantly to changes in dividend and interest rate.